Hypergeometric Forms of Well Known Partial Fraction Expansions of Some Meromorphic Functions (Global Journal of Science Frontier Research, 2011)
In this paper, we obtain hypergeometric forms of some meromorphic functions from .
Keywords: Maclaurin expansion; Mittag-Leffler theorem; Bernoulli and Euler numbers; Ramanujan’s transcendental functions